Conduction-based model of the Scrape-Off Layer power sharing between inner and outer divertor in diverted low-density tokamak plasmas. (May 2019) - Maurizio, R.; Duval, B.P.; Labit, B.; Reimerdes, H.; Theiler, C.; Tsui, C.K.; Boedo, J.; De Oliveira, H.; Février, O.; Sheikh, U.; Spolaore, M.; Verhaegh, K.; et al.
Highlights: Discussion of a simple model for the repartition of the Scrape-Off Layer exhaust power between the inner and outer divertors in a diverted low-density tokamak plasma. Found reasonable qualitative agreement with recent TCV experimental data and EMC3-Eirene simulations. Model capable of explaining the experimentally observed changes in the divertor power sharing with changes in the divertor magnetic configuration. TCV measurements show that, in attached conditions, a power exhaust solution at the outer divertor achieved via modifications of the magnetic configuration may come at the expense of the inner divertor. Abstract: A simple analytic model for the repartition of the Scrape-Off Layer (SOL) exhaust power between the inner and outer divertors in a diverted low-density tokamak plasma is introduced. Electron heat conduction is assumed to dominate the heat transport, from the outboard mid-plane to the divertor targets, with no heat sinks or sources in the SOL. Both divertor channels are in the attached, high-recycling regime. The model is in reasonable qualitative agreement with recent TCV experimental data and EMC3-Eirene simulations. For the Single Null divertor, it reproduces the experimentally observed increase in the power ratio between the inner and outer divertor plates of TCV, P in / P out, with increasing the outer divertor leg length or the outer target flux expansion. For the Snowflake Minus configuration, it reproduces the observed variation of P in / P out with X-point separation, although only for the reversed magnetic field direction. Within the model limitations, it provides a basic understanding of the power sharing in alternative divertor geometries.